Behavioral Intention to Use FinTech in Millennial Generation (Extension of TAM Model) - Yuhelmi, Yuhelmi; Puttri, Daniati; Kamela, Ice; Febriani, Febriani; Safitri, Nadia; Nurhuda, Nurhuda (JURNAL MANAJEMEN UNIVERSITAS BUNG HATTA, 2024)
This research aims to analyze the Behavioral Intention of the Millennial Generation in using FinTech as a payment platform and the factors that influence it by extending the TAM model. The extension variables of the TAM model are Trust, Habit, and Perceived Risk. The population in this study consisted of 521 Millennial generation respondents using purposive sampling. The analytical method used is the Structural Education Model (SEM) using Smart PLS. The research results found that the TAM model is a strong model for behavioral intentions to use FinTech, where Behavioral Intention to use FinTech is influenced by Perceived Ease of Use, Perceived usefulness, and Attitude. The findings for the extension variable are that Habit has a positive effect on behavioral intention to use FinTech, while Perceived Risk and Trust have no effect on behavioral intention or attitude in using FinTech